LEGAL PROTECTION FOR VICTIMS OF EXTRAJUDICIAL KILLINGS AS GROSS HUMAN RIGHTS VIOLATIONS IN INDONESIA - Ikhwani, Nurul; Farsia, Lena (Universitas Syiah Kuala, 2023)
This article examines the concept of extrajudicial killings and the legal protection available for victims of such heinous acts as gross human rights violations in Indonesia. The study adopts a normative approach, utilizing a comprehensive review of library, secondary, and tertiary legal materials to gather relevant data. The findings reveal that extrajudicial killings manifest in various forms, including genocide, crimes against humanity, enforced disappearance, torture, political assassination, and the excessive use of force, all of which meet the criteria for murder as defined by Law No. 26 of 2000. However, the existing legal protection for victims of extrajudicial killings falls short in fully guaranteeing their rights. The practical implementation of compensation, restitution, and rehabilitation measures encounters significant obstacles. Despite some efforts to address this issue, eradicating extrajudicial killings in Indonesia remains an ongoing challenge. The government must undertake further actions to effectively combat this grave violation of human rights